The role of the Republic of Korea in global governance: South Korean initiatives in the G20 - С.З. Ахметова (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
This article is devoted to determining the importance of the G-20 in global governance, as well as analyzing the initiatives proposed by the Republic of Korea on the margins of the G-20 summit to solve the complex problems of our time. The article applied a qualitative method, an analytical method, a generalization method and a comparative method were applied. The main part of the article tells the reader about the formation of the G20, the structure of the forum and the role at the present stage of human development, then the author studied in detail the results of the 2010 summit in Seoul. Attention was paid to the initiatives proposed by South Korea. Moreover, an average assessment of the success of the tasks approved by the members of the Group of 20 was identified.